57.4k views
4 votes
How can I simplify this and make sure to give a CLEAR explanation

How can I simplify this and make sure to give a CLEAR explanation-example-1

1 Answer

2 votes

Answer: 4x - 8

First, we use the property of distribution (its called something like that)

6 * x = 6x. 6 * 3 = 18. 6x - 18 - 2(x - 5)

We can also use the property of distribution on the other part.

2 * x = 2x. 2 * 5 = 10.

We then have the equation: 6x - 18 - 2x - 10.

18 - 10 = 8

6x - 8 - 2x

6x - 2x = 4x

4x - 8

User Panic
by
5.4k points